JMCR 2021
DOI: 10.7176/jmcr/76-04
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction and Customer Loyalty in the Post-Crisis Banking Sector of Ghana

Abstract: The banking industry is immensely important to the socioeconomic development of emerging economies by facilitating the exchange of money between depositors and borrowers. The banking industry in Ghana is facing corporate governance challenges, which has led to non-performance and subsequent withdrawal of operating licenses. The withdrawal of the licenses by the Bank of Ghana has impact on customer loyalty and satisfaction, which has not been significantly investigated in a post crisis banking sector of Ghana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…E-customer satisfaction is the customer's assessment regarding the etransaction in comparison to conventional transactions. According to Boateng et al (2021), Evanschitzky et al (2004), andSamsudeen et al (2020), the significant difference between e-retailing and traditional retailing services is transforming man to machine or transactions through artificial intelligence through the Internet. Therefore, for e-customer satisfaction, modified & innovative improvements are required, and this research bridges the gap between e-customers satisfaction and ecustomer loyalty.…”
Section: E-customer Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-customer satisfaction is the customer's assessment regarding the etransaction in comparison to conventional transactions. According to Boateng et al (2021), Evanschitzky et al (2004), andSamsudeen et al (2020), the significant difference between e-retailing and traditional retailing services is transforming man to machine or transactions through artificial intelligence through the Internet. Therefore, for e-customer satisfaction, modified & innovative improvements are required, and this research bridges the gap between e-customers satisfaction and ecustomer loyalty.…”
Section: E-customer Satisfactionmentioning
confidence: 99%
“…Previous literature emphasized the importance of Islamic e-banking as it permits customers can do transactions 24/7 without any hindrances by observing Islamic Laws. According to Boateng et al (2021), Butt (2018), Iqbal (2020), Dewi and Surabaya (2020), and Nguyen and Leblanc (2002), ecustomer loyalty increases when customer frequently uses e-banking services with satisfaction. Hence, it demonstrated that e-customer satisfaction is directly associated with ecustomer loyalty.…”
Section: E-customers Loyaltymentioning
confidence: 99%
“…[2] found that 40% of participants in his study want products that make their lives easier, 36% want simple to use products, 25% want products related to families and small households, and 25% desire custom-made products. [5] argue that customers also seek value-based items at the highest price, as well as products or services that provide physical or mental stimulation or reward throughout the purchasing experience. Satisfaction with a purchase can also be defined as an experience based on encounter or usage of a particular service [6], that results in customer loyalty [7], repeat purchases, positive word-of-mouth [8] and ultimately, greater accomplishments and profitability [9].…”
Section: Introductionmentioning
confidence: 99%